2017
DOI: 10.1016/j.tcb.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Bursting the Bubble – Nuclear Envelope Rupture as a Path to Genomic Instability?

Abstract: The nuclear envelope safeguards the genetic material inside the nucleus by separating it from the cytoplasm. Until recently, it was assumed that nuclear envelope breakdown occurs only in a highly controlled fashion during mitosis when the chromatin is condensed and divided between the daughter cells. However, recent studies have demonstrated that adherent and migrating cells exhibit transient nuclear envelope rupture during interphase caused by compression from cytoskeletal or external forces. Nuclear envelope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 64 publications
2
103
0
Order By: Relevance
“…The precise mechanisms by which NE damage and NE rupture cause DNA damage and cell death remains to be elucidated. The DNA damage could arise from exposure of genomic DNA to cytoplasmic nucleases following NE rupture, or nuclear exclusion and efflux of DNA repair factors, as previously discussed in the context of confined cell migration [75][76][77] . The close association of DNA damage with NE defects in our studies (Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms by which NE damage and NE rupture cause DNA damage and cell death remains to be elucidated. The DNA damage could arise from exposure of genomic DNA to cytoplasmic nucleases following NE rupture, or nuclear exclusion and efflux of DNA repair factors, as previously discussed in the context of confined cell migration [75][76][77] . The close association of DNA damage with NE defects in our studies (Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…We know that efficient DNA repair mechanisms to counteract the effects of replicative stress and other sources of damage are central to avoiding both premature ageing and cancer [11][12][13][14]. Recent in vitro studies using cancer cell lines and dendritic cells have shown that migration through micro capillaries imparts mechanical stresses on nuclei, and this can be a source of genome instability [1,2,[15][16][17]. If migrating cells in vivo, in particular stem cells, experience genome instability this has a number of broad implications for metazoan development and homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Metastasizing cancer cells that encounter tight interstitial spaces are particularly prone to transient NE rupture. This process is viewed as a new mechanism dependent on confinement that promotes genomic instability and tumor progression (Calero-Cuenca et al, 2018;Shah et al, 2017). Therefore, such a mechanism could be an important part of the tumor-promoting functions of Par3.…”
Section: Discussionmentioning
confidence: 99%